The tumor microenvironment in therapy resistance - Garcia, Guadalupe G.; Schmidt, Christopher J.; Hajal, Cynthia (Frontiers in Lab on a Chip Technologies, 2024)
Chemotherapy alone or in conjunction with surgery and radiation is often used to treat various cancer types. While effective at treating some tumors, the response varies across patients with different malignancies. For some cancers, such as glioblastoma, ovarian cancer, and soft tissue sarcoma, 85-100% of patients experience cancer recurrence and develop chemotherapy resistance, which often leads to worse prognoses. These alarming statistics highlight an urgent need to better understand the landscape of therapy resistance in cancer, in order to develop improved treatment strategies and prevent recurrence. A central focus has been the investigation of resistant tumor subclones and whether the use of different alkylating agents and/or immune checkpoint inhibitors can ablate different clones. However, very little effort has been directed towards studies of the tumor microenvironment, a complex ecosystem of blood vessels, fibroblasts, immune cells, signaling molecules, and extracellular matrix, in the context of therapy resistance. In this perspective, we provide an overview of different platforms, tools, and techniques that have been developed and used to identify tumor microenvironment alterations due to therapy resistance. We also address potential therapeutic strategies that involve components of the tumor milieu and have been identified and tested to overcome treatment-induced resistance. Identifying microenvironmental changes post-resistance presents opportunities for new targeted treatment strategies. The current state of the literature suggests a dire need for more engineered models that probe specific microenvironment contributors to therapy resistance or ways in which the tumor tissue can be harnessed to mitigate resistance.